Opportunity Assessment Framework for a Grocery Store in Adelaide, South Australia - Ahmadi Usman; Ria Triwastuti (Universitas Airlangga, 2019)
This research aims to discuss opportunity assessment framework for a grocery store business in Adelaide, South Australia. The method used in this research is that three existing opportunity assessment methodologies are initially selected and then validated to the manager of a grocery store by using a direct interview method. The result of this research is that a new and specific opportunity assessment framework with a weighted score will be formulated for the grocery store business. This new framework will be a combination of the three alternate methodologies and additional criteria suggested by the manager of a grocery.